2002
DOI: 10.1016/s1535-6108(02)00183-6
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of normal human cells in the absence of telomerase activation

Abstract: Our knowledge of the transformation process has emerged largely from studies of primary rodent cells and animal models. However, numerous attempts to transform human cells using oncogene combinations that are effective in rodents have proven unsuccessful. These findings strongly argue for the study of homologous experimental systems. Here we report that the combined expression of adenovirus E1A, Ha-RasV12, and MDM2 is sufficient to convert a normal human cell into a cancer cell. Notably, transformation did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
139
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 60 publications
14
139
2
2
Order By: Relevance
“…Because NAC was effective in blocking oncogene-induced chromosomal instability, it is likely that an additional stochastic event occurred in vivo for this single tumor to have formed. It is noteworthy that transformation of cells by coexpressing two or more genetic elements resulted in tumor cell populations that were polyclonal (Hahn et al 1999;Seger et al 2002). However, the pervasive nature in which oncogenic Ras and E1A induce chromosomal instability and karyotypic change demonstrates that tumor cells can undergo additional genetic alterations but still be polyclonal.…”
Section: Chromosomally Stable Serum-free Mouse Embryo Fibroblasts Arementioning
confidence: 99%
See 2 more Smart Citations
“…Because NAC was effective in blocking oncogene-induced chromosomal instability, it is likely that an additional stochastic event occurred in vivo for this single tumor to have formed. It is noteworthy that transformation of cells by coexpressing two or more genetic elements resulted in tumor cell populations that were polyclonal (Hahn et al 1999;Seger et al 2002). However, the pervasive nature in which oncogenic Ras and E1A induce chromosomal instability and karyotypic change demonstrates that tumor cells can undergo additional genetic alterations but still be polyclonal.…”
Section: Chromosomally Stable Serum-free Mouse Embryo Fibroblasts Arementioning
confidence: 99%
“…An extensive body of evidence has shown that several cooperating genetic elements can lead to the in vitro transformation of rodent and human cells (Land et al 1983;Ruley 1983;Hahn et al 1999;Rich et al 2001;MacKenzie et al 2002;Seger et al 2002). However, it has been more difficult to define the contribution of gross genetic alterations that are characteristic of nearly every tumor cell.…”
Section: Oncogenes Collaborate With Chromosomal Instability During Tumentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results, however, suggest that telomerase activity is not an obligate requirement for initial tumor formation under certain circumstances (Seger et al 2002). The co-expression of the adenovirus E1A oncoprotein and RAS suffices to induce anchorage-independent growth of BJ cells in soft agar.…”
Section: Htertmentioning
confidence: 99%
“…However, these cells undergo crisis either after extended passaging in vitro (40-50 PDs) or after explantation into culture. Cells which survive this period of crisis show telomerase activity (Seger et al 2002).…”
Section: Htertmentioning
confidence: 99%